Bagrada Bug, Painted Bug, Bagrada Hilaris (Burmeister) (Insecta: Hemiptera: Pentatomidae) - Eric LeVeen; Amanda C. Hodges (EDIS)
The bagrada bug is a pest of concern to Florida agriculture, and there are several similar species with which it may be confused. Bagrada bugs have been detected on plant material in trucks traveling across state borders. Twelve interceptions have been made from 2011-2013 at the FDACS agricultural inspection stations along the interstate at the Florida border. Due to the number of recent interceptions, and the ability of this pest to feed on many plants, the bagrada bug has potential to establish in Florida. Therefore, monitoring, surveillance, and educational efforts have begun in Florida to facilitate early detection and rapid response as the spread of the bagrada bug continues to other areas. This 7-page fact sheet was written by Eric LeVeen and Amanda C. Hodges, and published by the UF Department of Entomology and Nematology, July 2014.